Problems of monotony diagnostics - Bagdonas, A. (Psichologija, 1983)
The article reviews problems of monotony diagnostics. Three aspects of the diagnostics are singled out: (1) estimation of the state of monotony based on the indices of the efficiency of performance and on the parameters of physiological and psychical functions (the psychological diagnostics of monotony is divided into subjective and objective psychometry); (2) estimation of the job and performance monotony based on the technological indices of work operations and on the decrement of performance efficiency or optimal functional states; (3) estimation of the satisfaction in monotonous work, of the attitude towards it and of the monotonophilic – monotonophobic personality tendencies. The results of monotony investigation conducted in the Laboratory of Special Psychology of Vilnius University are presented.